Combination of Fuzzy Weighted Product and Entropy in Determining the Eligibility of Poor Rice Recipients - Intan Zahira; Sriani Sriani (Research Group of Data Engineering, Faculty of Informatics, 2025)
The Indonesian currency crisis caused a significant decline in food production, which ultimately resulted in increased costs and reduced purchasing power for all basic needs. Therefore, the government is trying to launch a poverty alleviation program in the form of a social assistance program for the poor in the form of rice to ease the burden on poor families and increase their access to food that is essential for life. In order to avoid problems of inconsistency in the recipients of this assistance, a decision support system was created to determine the eligibility of recipients of poor rice assistance so that it is right on target. In determining the recipients of this social assistance, evaluation criteria are needed. The evaluation criteria required are income, age, dependents, occupation and status. The researchers developed a system that combines the weighting method (Entropy) and the decision method (Fuzzy Weighted Product) to determine recipients of social assistance. Where the data is converted into fuzzy numbers first and then processed with the decision method with the final weight of the entropy weighting method. The combination method of Fuzzy Weighted Product (F-WP) and Entropy allows for optimal selection of recipients of social assistance for the poor, and an automatic selection system that can be used by administrators to streamline the process in each district. The selection results data will be available to all registered users, sorted from highest to lowest according to target ranking, to fairly determine who will receive social assistance.